Vital rate estimates for the common eider Somateria mollissima, a data‐rich exemplar of the seaduck tribe. Issue 4 (2nd December 2021) - Nicol‐Harper, Alex; Wood, Kevin A.; Diamond, Antony W.; Major, Heather L.; Petersen, Aevar; Tertitski, Grigori; Doncaster, C. Patrick; Ezard, Thomas H. G.; Hilton, Geoff M.
Abstract: This database collates vital rate estimates for the common eider ( Somateria mollissima ), providing a complete demographic parameterization for this slow life‐history species. Monitored across its circumpolar range, the common eider represents a data‐rich exemplar species for the less‐studied seaducks, many of which are under threat. The database contains estimates of the following vital rates: first‐year survival; second‐year survival; adult annual survival; first breeding (both age‐specific recruitment probability, and breeding propensity across potential recruitment ages); breeding propensity of established female breeders; clutch size; hatching success; and fledging success. These estimates are drawn from 134 studies, across the scientific and grey literature, including three previously inaccessible datasets on clutch size that were contributed in response to a call for data through the IUCN Species Survival Commission's Duck Specialist Group. Although clutch size has been much studied, the contributed datasets have enhanced coverage of studies reported in non‐English languages, which were otherwise only represented when cited in English‐language publications. Breeding propensity has been little studied, perhaps because adult females are often assumed to attempt breeding every year; we obtained a mean breeding propensity of 0.72. Our synthesis highlights the following gaps in data availability: juvenile and male survival; population change; and studies from Russia (at least accessible in English). The database is intended to serve population modellers and scientists involved in the policy and practice of seaduck conservation and management. Abstract : We present a database collating demographic information for the common eider ( Somateria mollissima ), as an exemplar of lesser‐studied seaducks. Vital rates included: 1 st ‐year survival, 2 nd ‐year survival, adult annual survival, recruitment, adult female breeding propensity, clutch size, hatching success, fledging success. We hope that this synthesis will be useful for population modellers and managers, but note relative data gaps for juvenile and male survival, population growth estimates, and data from Russia. Photo credit: Kate Evans/WWT.